Albert Nobbs [videorecording (DVD)] - García, Rodrigo, 1959-; Close, Glenn, 1947-; Close, Glenn, 1947-; Wasikowska, Mia, 1989-; Taylor-Johnson, Aaron, 1990-; McTeer, Janet; Rhys-Meyers, Jonathan, 1977-; Fricker, Brenda; Collins, Pauline, 1940- (Lionsgate, 2012)
A woman passes as a man in order to work and survive in 19th century Ireland. Some thirty years after donning men's clothing, she finds herself trapped in a prison of her own making.